Kinematics and Laxity of the Ankle Joint in Anatomic and Nonanatomic Anterior Talofibular Ligament Repair: A Biomechanical Cadaveric Study. Issue 3 (March 2019) - Shoji, Hiroaki; Teramoto, Atsushi; Sakakibara, Yuzuru; Kamiya, Tomoaki; Watanabe, Kota; Fujie, Hiromichi; Yamashita, Toshihiko
Background: Although it is crucial to accurately identify the anterior talofibular ligament (ATFL) attachment site, it may not be feasible to fully observe the ATFL attachment site during arthroscopic surgery. As a result, the repair position might often be an unintentionally nonanatomic ATFL attachment site. Hypothesis: Anatomic ATFL repair restores kinematics and laxity to the ankle joint, while nonanatomic ATFL repair does not. Study Design: Controlled laboratory study. Methods: Seven normal fresh-frozen human cadaveric ankles were used. The ankles were tested with a 6 degrees of freedom robotic system. The following ankle states were evaluated: intact, ATFL injured, ATFL anatomic repair, and ATFL nonanatomic repair. The ATFL nonanatomic repair position was set 8 mm proximal from the center of the ATFL attachment site of the fibula. For each state, a passive plantarflexion (PF)–dorsiflexion (DF) kinematics test and a multidirectional loading test (anterior forces, inversion moment, and internal rotation moment) were performed. Results: The kinematics and laxity of the anatomic repair were not significantly different from those of the intact state. In nonanatomic repair, the inversion-eversion angle showed significant inversion (3.0°-3.4°) from 5° to 15° of DF, and the internal rotation–external rotation angle showed significant internal rotation (2.0°) at neutral PF-DF versus the intact state. In addition, internal rotation laxity was significantly increased (5.5°-5.8°) relative to the intact state in the nonanatomic repair at 30° and 15° of PF. There were no significant differences in anterior-posterior translation between the repairs. Conclusion: Although the anatomic ATFL repair state did not show significant differences in kinematics and laxity relative to the intact state, the nonanatomic ATFL repair state demonstrated significant inversion and internal rotation kinematics and internal rotation laxity when compared with the intact state. Clinical Relevance: Nonanatomic repair alters kinematics and laxity from the intact condition.